Changes in phenolic composition and antioxidant activity during germination of quinoa seeds (Chenopodium quinoa Willd.) - Carciochi, Ramiro Ariel (2014)
Quinoa seed (Chenopodium quinoa Willd.) has obtained great interest in recent years due to its high nutritional value and its content of natural antioxidants and other phytochemicals with positive biological activity in humans. Their ability as health promoters depends strictly on the processing conditions to which the seeds are submitted. In this work, quinoa seeds were subjected to germination and subsequent oven-drying at 40ºC in order to evaluate changes on phenolic compounds composition as well as on the antioxidant activity along different germination stages. Germination resulted in a 2 fold increase in antioxidant activity measured as DPPH radical scavenging activity, after 3 days of germination. At the same time, the amounts of HPLC identified phenolic acids and flavonoids increased 8.57 fold, and 4.4 fold respectively. Germination and subsequent oven-drying was shown to be a good process to improve the phenolic content and antioxidant activity of quinoa seeds, and thereby obtain an ingredient to be used in functional food formulations.